Simultaneous Inoculation of Malbec (Vitis vinifera) Musts with Yeast and Bacteria: Effects on Fermentation Performance, Sensory and Sanitary Attributes of Wines - Massera, Ariel Fernando; Soria, Adriana; Catania, Carlos; Krieger, Sibylle; Combina, Mariana (Faculty of Food Technology and Biotechnology, University of Zagreb (Croacia), 2021)
Malolactic fermentation has important consequences for the quality of wine. The present study analyzes the effect of timing of inoculation with bacteria on the performance of alcoholic and malolactic fermentation in Malbec musts from a warm climate wine growing region during two consecutive vintages, with a specific consideration for the sensory and sanitary wine parameters. In this study traditional vinification, where malolactic bacteria were inoculated after the completion of alcoholic fermentation, was compared with a simultaneous inoculation with yeast and bacteria. The experiment was made on pilot scale which closely reproduces winery conditions. The obtained results point out that simultaneous inoculation resulted in a reduction of total time of fermentation and a better control of the malolactic fermentation due to the early dominance of a selected bacterial strain. There were no negative effects on yeast population and alcoholic fermentation performance observed. Differences between the wine sensory attributes were no significant or they were in favour of simultaneous inoculations. No statistical differences in the biogenic amine levels between different timings of inoculation were found.